Delegated Monitors, Large and Small: Germany's Banking System, 1800–1914 - Guinnane, Timothy W (Journal of Economic Literature, 2002)
Banks play a greater role in the German financial system than in those of the United States or Britain. Germany's large universal banks are admired by those who advocate bank deregulation in the United States. Others admire the universal banks for their supposed role in corporate governance and industrial finance. Many discussions distort the German banking system by overstressing one of several types of banks, and ignore the competition and cooperation between the famous universal banks and other banking groups. Tracing the historical development of the German banking system from the early nineteenth century places the large universal banks in context.